Multiple network organohydrogels with high strength and anti-swelling properties in different solvents. (June 2021) - Wu, Qingshan; Qi, Shuanhu; Zhao, Tianyi; Yan, Hao; Liu, Mingjie
Abstract: Compared to traditional hydrogel materials, organohydrogels have wider applications due to their special properties such as abilities of self-adaptive, freeze-tolerant and mechanically stable over a wide range temperature. In this paper, we prepared Poly (vinyl alcohol)/Poly (butyl methacrylate)-co-Poly (lauryl methacrylate) multiple network organohydrogels (MN-OHGs) by multiple swelling polymerization method. By tuning the components of heterogeneous networks, the swelling behaviors and the surface wettability in different solvents of MN-OHGs could be controlled. When the ratio of oleophilic polymer network (OPN) content to hydrophilic polymer network (HPN) content was 1:1.4, the MN-OHGs showed the highest mechanical properties (the elastic modulus could reach 8 MPa, and the toughness could reach 12 MJ/m 3 ). Moreover, when the OPN/HPN ratio was 2/1, the MN-OHGs could maintain a stable volume in artificial seawater with mechanical properties enhanced by 47.3%. These characteristics demonstrated that the MN-OHGs were ideal candidates for functional materials which could be applied in complex environments. Graphical abstract: Image, graphical abstract